Motivation Improvement and Student Learning Outcomes in Science Learning Using Explicit Model Instruction in Basic Class IV Class - Wellindi Cintita Viani (Postgraduate School, Universitas Negeri Padang, 2019)
Abstract: Based on observations and interviews with researchers at SDN 01 shadow, researchers found that the problems regarding student learning motivation were still low. The research problem formulation is how to increase student motivation and learning outcomes in science learning through the Explicit Instruction model. The benefits of this research are for theoretical and practitioner interests. This type of research is Classroom Action Research. The subjects of this study were grade IV students of 21 people. The research instruments used were motivation observation sheets, teacher activity observation sheets, motivational questionnaire sheets, and student learning outcomes test sheets. From the results of the study, the percentage of motivation asked by the first cycle numbered 45.22%, and the second cycle 71.42%, the percentage of student motivation in answering and responding to the first cycle questions 45.22%, and the second cycle 83.32%, student motivation in expressing opinions in the first cycle 52.35%, and the second cycle 83.33%, doing the exercises on time in the first cycle was 61.9%, and the second cycle 78.57%. So science learning with the Explicit Instruction model (direct teaching) can increase student motivation and learning outcomes.